Presynaptic I(1)-Imidazoline Receptors Reduce GABAergic Synaptic Transmission in Striatal Medium Spiny Neurons - Tanabe, Mitsuo (J Neurosci, 2006)
Imidazoline receptors are expressed widely in the CNS. In the present study, whole-cell patch-clamp recordings were made from medium spiny neurons in dorsal striatum slices from the rat brain, and the roles of I(1)-imidazoline receptors in the modulation of synaptic transmission were studied. Moxonidine, an I(1)-imidazoline receptor agonist, decreased the GABA(A) receptor-mediated IPSCs in a concentration-dependent manner. However, glutamate-mediated EPSCs were hardly affected. The depression of IPSCs by moxonidine was antagonized by either idazoxan or efaroxan, which are both imidazoline receptor antagonists containing an imidazoline moiety. In contrast, yohimbine and SKF86466 (6-chloro-2,3,4,5-tetrahydro-3-methyl-1H-3-benzazepine), which are α2-adrenergic receptor antagonists with no affinity for imidazoline receptors, did not affect the moxonidine-induced inhibition of IPSCs. Moxonidine increased the paired-pulse ratio and reduced the frequency of miniature IPSCs without affecting their amplitude, indicating that this agent inhibits IPSCs via presynaptic mechanisms. Moreover, the sulfhydryl alkylating agent N-ethylmaleimide (NEM) significantly reduced the moxonidine-induced inhibition of IPSCs. Thus, the activation of presynaptic I(1)-imidazoline receptors decreases GABA-mediated inhibition of medium spiny neurons in the striatum, in which NEM-sensitive proteins such as G(i/o)-type G-proteins play an essential role. The adenylate cyclase activator forskolin partly opposed IPSC inhibition elicited by subsequently applied moxonidine. Furthermore, the protein kinase C (PKC) activator phorbol 12,13-dibutyrate attenuated and the PKC inhibitor chelerythrine potentiated the moxonidine-induced inhibition of IPSCs. These results suggest that IPSC inhibition via presynaptic I(1)-imidazoline receptors involves intracellular adenylate cyclase activity and is influenced by static PKC activity in the striatum.